Travel Fund (Review of Economic Studies, 2001)
Journal Article Travel Fund Get access The Review of Economic Studies, Volume 68, Issue 1, January 2001, Page 231, https://doi.org/10.1111/restud/68.1.231 Published: 01 January 2001